Applied conversation analysis social interaction in institutional settings - Lester, Jessica Nina; O'Reilly, Michelle (Los Angeles SAGE, 2019)
"Focusing on applied conversation analysis (CA), this timely book offers practical insights and guidelines for CA scholars studying social interactions in institutional settings. Written in an accessible style and packed with case studies, examples, activities, and practical tips, the book takes readers through the entire process of planning and carrying out an applied CA research study. By highlighting challenges, debates, and important questions, each chapter provides the theoretical foundation necessary for making informed decisions at every stage of a research project. The book is divided into three sections (context and planning, doing a project using conversation analysis, and disseminating your research) to mirror the research process."--Provided by publisher.
Includes bibliographical references (pages 271-285) and index.
Keywords: Conversation analysis